In Search of Profits: Measuring Income from the Unrelated Commercial Use of a Tax-Exempt Organization's Assets - Sansing, Richard C. (The Accounting Review, 2001)
Profits a tax-exempt organization earns from business activities that are not related to the organization's exempt purpose are subject to the unrelated business income tax (UBIT). This paper shows that when the taxable and tax-exempt activities are substitutes, taxable income exceeds the incremental pretax financial return from the unrelated business activity because the exempt organization cannot deduct the opportunity cost of lost exempt function revenues when computing UBIT. As a result, the exempt organization may: (1) reduce or eliminate its unrelated business activity, or (2) change the way it uses its assets for unrelated business purposes by licensing the use of its assets to an unrelated taxable organization in exchange for nontaxable royalties. The model shows that although UBIT may distort the way in which an exempt organization uses its assets, this distortion can increase social welfare.